Great state China and the world - Brook, Timothy 1951- (Profile Books Ltd, 2019)
China is one of the oldest states in the world. It achieved its approximate current borders with the Ascendancy of the Yuan dynasty in the thirteenth century, and despite the passing of one Imperial dynasty to the next, has maintained them for the eight centuries since. China remained China through the Ming, the Qing, the Republic, the Occupation, and Communism. But despite the desires of some of the most powerful people in the Great State through the ages, China has never been alone in the world. It has had to contend with invaders as well as foreign traders and imperialists. Its rulers for the majority of the last eight centuries have not been Chinese. China became a mega-state not by conquering others, Timothy Brook contends, but rather by being conquered by others and then claiming right of succession to the empires of those Great States. What the Mongols and Manchu ruling families wrought, the Chinese ruling families of the Ming, the Republic, and the People's Republic, have perpetuated. Yet a contemporary Chinese idea of a 'fatherland' that is, and always has been, completely and naturally Chinese persists. Brook argues that China, like everywhere, is the outcome of history, and like every state, rests on its capacities to conquer and suppress. In The Great State, Brook examines China's relationship with the world at large for the first time, from the Yuan through to the present, by following the stories of ordinary and extraordinary people navigating the spaces where China met, and continues to meet, the world